ANALISIS PENGARUH LIKUIDITAS, LEVERAGE, DAN INFLASI TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK - Wanda Salsabila Putri (2022)
This research is quantitative research that aims among other things to determine the effect of liquidity, leverage, and inflation of the financial distress. The population used in this study is the transportation and logistic industry companies with a total of 30 companies listed on the Indonesia Stock Exchange for the 2017-2021 period. To obtain a sample point, this study used a purposive sampling method so as to obtain a sample point of 16 companies. The hypothesis testing tool used is logistic regression analysis using E-views 12.0 software. The results of the rest were obtained (1) liquidity has significant effect on financial distress, (2) leverage has no significant effect on financial distress, (3) inflation has no significant effect on financial distress. Keywords: Liquidity, Leverage, Inflation and Financial Distress